Sense of coherence (SOC) and styles of coping in patients with the diagnosis of ovarian carcinoma or testicular cancer - Kurowska, Krystyna; Jaworska, Mirosława (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. The level of the Sense of Coherence (SOC) influences the ability to cope with stress. High SOC level makes people believe in life predictability and order which in turn motivates them to be healthy and functional. Aim of the study. The aim of the study was to estimate the level of SOC and styles of coping with disease and stress related to it in patients undergoing therapy for genital cancer. Material and methods. The study included 78 patients undergoing therapy in Oncology Center, Bydgoszcz. SOC level was assessed using Antonovsky SOC-29 questionnaire and coping with stress was estimated using CISS questionnaire. Results. Patients with a diagnosis of genital cancer have lowered SOC level. Patients with higher SOC levels more often choose task-oriented style of coping and more rarely emotionally-based style. Conclusions. Estimation of the levels of SOC and social support might be used as determinant of care of patients with cancer at different stages of the disease. Nursing Topics 2010; 18 (4): 429-434